Migration in Lusophone Cinema - Wood, Naomi (Imagofagia, 2021)
Sobre: Rêgo, Cacilda e Brasileiro, Marcus, Eds. Migration in Lusophone Cinema, New York: Palgrave Macmillan, 2014, 232pp., ISBN 978-1-137-40891-4